Exotisme et altérité: Essai sur les fondements d'une critique de l'anthropologie - Affergan, Francis (Sociologie d'aujourd'hui, 1987)
Keywords: anthropologie; approches et analyses; cours; discipline; har4610; histoire et politique; premier cycle; racisme; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Visions partielles, visions partiales: visions des minoritaiers en sociologies - JUTEAU-LEE, Danielle (Sociologie et sociétés, 1981)
Résumé L'irruption du discours des minoritaires en sociologie fait éclater le discours des majoritaires en provoquant la remise en question de leurs explications à tendance naturaliste, culturaliste et psychologisante. Affichant le caractère partiel et partial de leurs visions, les femmes et les "ethniques" favorisent l'éclosion de synthèses provisoires, susceptibles de rendre compte des formes multiples de l'oppression
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; patriarcat; point de vue situé; pol4212; premier cycle; racisme; sciences humaines; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; universalisme